PEMBENTUKAN KARAKTER RELIGIUS SANTRI BERBASIS METODE KHOLWAT - Moh Ismail; Djamali; Harits Nu'man (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2022)
Character education has a role in building religious character for students, one of which is to improve moral habits for students. In addition, the formation of religious character can be built through the kholwat method which focuses on good spiritual attitudes for students' habits. This research method uses the library research method, namely research carried out using literature, both in the form of books, notes, and reports on research results and previous research. The results of this study can conclude the process of implementing the kholwat method in shaping the religious character of students by means of intention, fasting, speaking less, tawasul and dhikr, reducing sleep at night, reducing eating and drinking, daimul ablution, not taking a bath during the day, taking a bath with the intention of repentance at at night, sunnah prayers, and meditation.